Optimizing the Entropy of the Unsteady Flow of Ternary Nanofluids in an Inclined Conduit: Smart Pumping Using Electro-Osmotic Flow - Reima D. Alsemiry; Essam M. Elsaid; S. A. Alharbi; Mohamed S. Abdel-Wahed (International Journal of Mathematics and Mathematical Sciences, 2024)
The purpose of this study is to investigate the flow of liquid (specifically water) supported by three different types of nanoparticles (copper, silver, and aluminum oxide) in a slanted microcorrugated pipe with varying diameters and wave displacements. This model fulfills several key uses in the fields of environmental and water treatment, such as improving fluid mixing within inclined microchannels to boost the effectiveness of filtration and separation processes and designing inclined channels with ripples to better mix waste materials and more effectively separate different components. In this perception, we analyzed a model for the fluids flow inside the microchannel with the electromagnetic field (EMF) effects and pressure variation in the conduit under the external influence of thermal radiation and heat source which did not appear in the last published literature. The analytical techniques with assistance of mathematical software were used to solve the main governing equations such as Poisson, momentum, and energy equations and then deduce the heat transfer rate at the peristaltic conduit surfaces and the system’s ideal entropy. The results of the model simulation suggested that a number of factors could have a big influence on how thermal systems are built. It was claimed that the irreversibility resulting from friction and Joule heating, as opposed to thermal irreversibility, controls the system’s entropy buildup more tightly. Furthermore, the alteration of the conduit’s form and geometry resulted in a substantial enhancement in the heat transfer rate at its bottom wall, ranging from 20% to 600%. Despite numerous studies, an accurate model regarding the mechanism of the liquid’s flow supported by tri-nanoparticles in an inclined microcorrugated conduit enclosing variable diameters and wave shifts is far from being understood.